Structural diversity among Acinetobacter baumannii K-antigens and its implication in the in silico serotyping - Roshini, Janardhanaachari; Patro, L. Ponoop Prasad; Sundaresan, Sruthi; Rathinavelan, Thenmalarchelvi (Frontiers in Microbiology, 2023)
Acinetobacter baumannii is an emerging opportunistic pathogen. It exhibits multi-, extreme- and pan-drug resistance against several classes of antibiotics. Capsular polysaccharide (CPS or K-antigen) is one of the major virulence factors which aids A. baumannii in evading the host immune system. K-antigens of A. baumannii exploit the Wzx/Wzy-dependent pathway that involves 13 different proteins for its assembly and transport onto the outer membrane. 64 (out of 237 K-locus(KL) types) known K-antigen sugar repeating structures are discussed here and are classified into seven groups based on their initial sugars, QuiNAc4NAc, GalNAc, GlcNAc, Gal, QuiNAc/FucNAc, FucNAc and GlcNAc & Leg5Ac7Ac/Leg5Ac7R. Thus, the corresponding seven initializing glycosyltransferases (ItrA1, ItrA2, ItrA3, ItrA4, ItrB1, ItrB3 and ItrA3 & ItrB2) exhibit serotype specificity. The modeled 3D-structural repository of the 64 K-antigens can be accessed at: https://project.iith.ac.in/ABSD/k_antigen.html. The topology of K-antigens further reveals the presence of 2-6 and 0-4 sugar monomers in the main and side chains respectively. The presence of negatively (predominant) or neutrally-charged K-antigens is observed in A. baumannii. Such diversity in the K-antigen sugar composition provides the K-typing specificity (viz., 18-69% in terms of reliability) for Wza, Wzb, Wzc, Wzx and Wzy proteins involved in the Wzx/Wzy-dependent pathway. Interestingly, the degree of uniqueness of these proteins between different K-type is estimated to be 76.79% considering the 237 reference sequences. This article summarizes the A. baumannii K-antigen structural diversity and creation of a K-antigen digital repository and provides a systematic analysis of the K-antigen assembly and transportation marker proteins.